Alfalfa but not milk in lamb's diet improves meat fatty acid profile and α-tocopherol content. (May 2018) - Álvarez-Rodríguez, J.; Ripoll, G.; Lobón, S.; Sanz, A.; Blanco, M.; Joy, M.
Abstract: To establish animal feeding recommendations, it is required to quantify whether the effects of combining dietary alfalfa and milk on meat composition of light lambs are overlapped or independent. This experiment aimed to evaluate the separate effects of dietary alfalfa and milk access on the light lamb carcass quality (10–11 kg), meat colour, chemical composition, fatty acid profile and α-tocopherol content. Thirty-two lambs were assigned to one of four treatments in a 2 × 2 factorial design. The factors were the inclusion of dietary forage (grazed alfalfa vs. concentrate-fed indoors) and lactation length (weaning at a target live-weight of 13 kg vs. suckling until slaughter at 22–24 kg). Dietary alfalfa but not milk supply improved conjugated linoleic acid isomers (CLA), omega-3 fatty acids and α-tocopherol contents in lamb meat without affecting meat colour attributes. Milk supply affected more the fatty acid profile (more saturated) than the α-tocopherol content of meat. Thus, dietary alfalfa improved CLA, omega-3 fatty acids and α-tocopherol content in light lamb without affecting the meat colour, whereas lengthening the lactation period did not provide benefits in terms of meat colour or healthy nutrient composition. Graphical abstract: Highlights: Dietary alfalfa has no detrimental effects on light lamb meat colour. Dietary alfalfa increases vitamin E, CLA isomers and omega-3 in lamb meat. Long lactation has no benefits for lamb meat colour. Long lactation has no benefits for lamb meat fatty acids and vitamin E content.